Sistem Informasi Pemesanan Jasa Fotografer Berbasis Web Pada Studio Fotograferku - Indra Astutik, Ika Ratna; Wignya Radhitya, Yudhistira (Indonesian Journal Publisher, 2024)
Studio Fotograferku is a company engaged in photography services. In the current digital era, the need for photography services continues to increase along with the growth of the creative industry and social media. However, the process of finding and ordering photographers often takes a long time and is less efficient. Seeing this potential, we developed a web-based photographer ordering information system. This system aims to make it easier for customers to search, compare, and order photographer services according to their needs and preferences. This system provides a photographer search feature based on category, location, price, and portfolio. Custome can view profiles, works and reviews of available photographers. In addition, this system is equipped with a calendar feature that allows customers to see the availability of dates from photographers and place orders directly through the platform. To increase user trust, the system is also equipped with a rating and review system that can assist customers in making decisions. From the photographer's perspective, they can register themselves, manage their profile, upload their portfolio, and schedule their activities. This system is also equipped with a notification feature to inform photographers about new orders or changes to existing orders. This web-based photographer ordering information system is expected to be a bridge between photographers and customers, increase efficiency in the ordering process, and expand market reach for photographers.